PENGARUH METODE PEMBELAJARAN EKLEKTIK TERHADAP HASIL BELAJAR BAHASA ARAB SISWA MADRASAH TSANAWIYAH MAHAD HADITS AL-JUNAIDIYAH BIRU BONE - A. FAJAR AWALUDDIN (Institut Agama Islam Negeri (IAIN) Bone, 2018)
Thisresearch aimsto knowthe effect of learning method towardthe studentsArabicachievementinthe fifth gradeof Islamic Junior HighSchool(Madrasah Tsanawiyah)Al-Junaidiyah Biru Bone for academic year2017/2018. The research questions were: is there any difference in Arabic learning achievement as a whole between a group of students who have been given intiqiyyah methods and another group of students who have been given conventional methods. This research was an experimental study using randomized control group design. The influencing factorial variable is learning methods on Arabic. The Arabic learning achievement was used to know the students? skill or capability Arabic learning. In experimental class, intiqiyyah methods as experiment methods, and conventional methods as control methods. This research concluded that there was any difference between students Arabic achievements of group of students who have been given intiqiyyah methods and group of students who have been given conventional methods.